Development and Quality Analysis of Laboratory Management Information System Based on CodeIgniter Framework - Nafi’ah, Rahmawati; Dewanto, Adi; Sugiantoro, Bambang (Proceeding International Conference on Science and Engineering, 2020)
The objectives of the research are designing and create a laboratory information management system (SIMLAB) based on codeIgniter framework, and ensure the software quality based on Web-QEM standarts. It was built to help facilitate the process of laboratory management in SMK X in Yogyakarta City. The problems that occur in SMK X are the recording of inventory, borrowing and returning equipment is still processed manually on books that have not been able to support service flexibility and data security. The type of this research is Research and Development (R&D) with waterfall development model. The phases of this development model include analysis, design, coding, and testing. The analysis stage include literature study, field studies, user analysis, software analysis, and hardware analysis. Planning stages include database design using ERD, interface design, and modeling with UML. Coding stage uses the Code Igniter framework for back-end, Bootstrap framework as a supporting front-end framework, and My SQL relational database. Testing stage uses the quality standards of Web-QEM. The results of this research are (1) laboratory management information system developed by some features: laboratory information, scheduling, guest books, inventory, loan, return, and maintenance equipment. (2) The quality test result of functionality characteristic gave 100% (very suitable), reliability gave 100% (satisfy), usability gave 83.4% (very suitable), efficiency characteristic using YSlow gave 95.2% (very suitable), and using Page Speed gave 95.7% (very suitable) with 0.6 seconds for load time (accepted). Base on the test could be concluded that the laboratory information management system meets the quality standards of Web-QEM.